Reliability and validity of peer aggression coping self-efficacy scale - Shafie, Amin Al Haadi; Mahmud, Zuria; Amat, Salleh; Mohd Salleh, Amla; Jusoff, Kamaruzaman; Ahmad Ibrahim, Mizan Adiliah (IDOSI Publications, 2011)
Worldwide, most of the mainstream media commonly reports bullying behavior. Nevertheless the instruments for measuring bullying behavior and the attitude towards bullying behavior among Malaysian adolescents are lacking. This study examined the reliability and validity of the peer aggression coping self-efficacy scale measuring the self-efficacy of bully victims among Malaysian adolescents. The scale, which consists of 45 items, was translated to Malay language using back translation method and its validity was examined using 176 high school students. The split-half reliability result revealed Cronbach’s alpha of 0.91, indicating a high reliability. Four experts in the counseling field established face validity. The Peer Aggression Coping Self-Efficacy Scale provides a useful measure for examining children’s self-efficacy.